Secagem de cevada: análise da anatomia e do meio de transporte - Felizardo, Marcos Paulo (2018)
Despite the recent motivations for application in the food industry, the characterization of polished barley grains is still scarce in the literature. In this way, the objective of this work was the experimental analysis of the effects of the plant anatomy and the transport medium on the drying process of the barley grains. The polishing experiments of the barley grains were carried out in rotary drum coated with sandpaper. Experiments were carried out to evaluate the extensive physical characteristics of barley grains at different polishing levels and ground barley grains and their parts, as well as the characterization of the physical properties of the porous media formed for these materials. For these materials, the transport properties were measured, such as: effective thermal conductivity in stagnant medium, permeability, minimum fluidization velocity and effective mass diffusivity. Finally, the transfer of heat and mass to polished grains (without external tissues) and whole grains were evaluated by means of experimental measurements. In addition, the drying media were compared with isolated submerged particle, fluidized bed, fixed bed with interstitial flow (perpendicular) and fixed bed with tangential flow. It was verified that in different levels of polishing the variations were more significant in the thickness of the grains in relation to the other dimensions, besides this in the specific masses of the porous media were identified variations and these were correlated with the variations of the grains due to the polishing. The rotary drum polishing process allowed the removal of external tissues, where for 5 days of polishing the effects of these tissues on the properties of the polished grains were not observed. For this time was removed (24.2 ± 3.6)% of surface mass. The discussion of heat transfer and mass was carried out through the characterization of the grains and drying media. The external tissues were shown to be a barrier to heat transfer and mass, besides being a superficial mechanical resistance in the barley grains.